Correlation analysis between gut microbiota characteristics and melasma - Liu, Cong; He, Dan; Yu, Anye; Deng, Yaru; Wang, Li; Song, Zhiqi (Frontiers in Microbiology, 2022)
In recent years, many studies have shown that the gut microbiota can affect the occurrence and development of a variety of human diseases. A variety of skin diseases are related to the regulation of the gut–skin axis, such as psoriasis, atopic dermatitis, and acne. Gut microbial dysbiosis can promote the development of these diseases. The gut microbiota can affect estrogen metabolism, β-glucuronidase secreted by the gut microbiota can promote the reabsorption of estrogen by the gut, and estrogen is transported to other parts of the body through the circulatory system. The occurrence and development of melasma are closely related to abnormal metabolism of estrogen. The relationship between the structure of the gut microbiota and melasma remains unclear. Epidemiological surveys were conducted in patients with melasma and healthy subjects (control group) in this study. The feces were collected for 16S rRNA sequencing analysis of the gut microbiota. To compare the similarities and differences in species diversity of the gut microbiota between these two groups, we calculated the α-diversity and β-diversity indices and analyzed the differences between them. We found that the abundance of Collinsella spp., Actinomyces spp. (belonging to Actinobacteria), Parabacteroides spp., Bacteroides spp., Paraprevotella spp. (belonging to Bacteroidetes), Blautia spp., and Roseburia spp. (belonging to Firmicutes) in the melasma group were significantly different compared with that in the healthy group. The largest difference was found in Actinobacteria (p<0.05), and there were also significant differences in the abundance of Coriobacteriia, Actinobacteria, Coriobacteriales, Coriobacteriaceae, and Collinsella spp. between the two groups (all p<0.05). Many of these differences in the microbiota were closely related to the production of β-glucuronidase and the regulation of estrogen synthesis or metabolism. Changes in the gut microbiota structure and the biological effects of Collinsella spp. in the microbiota in patients with melasma can play an important role in the occurrence and development of melasma by affecting the body’s estrogen metabolism. This study provides a theoretical basis and experimental data reference for future studies on the relationship between the gut microbiota and melasma, and may be helpful for the prevention and treatment of melasma.